Personality correlates in the tendency to incur debt in patients with and without osteoarthritis - Łukasiewicz, Jacek; Stencel, Marcin; Raczkowski, Adam; Cwynar, Andrzej; Cwynar, Wiktor; Saran, Tomasz; Mazur, Anna (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Osteoarthritis is the most common disease of the musculoskeletal system. Osteoarthritis progresses slowly, but with time it results in movement disability and chronic pain. Its progression is also significantly associated with personality functioning and the ability to make rational life choices regarding various aspects of human life, including the economic sphere. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of the research was to determine how personality correlates with a tendency towards indebtedness between patients with and without osteoarthritis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The researched sample consisted of two groups - 50 patients diagnosed with osteoarthritis hospitalized in the Department of General and Neuro Rehabilitation in the Institute of Rural Health in Lublin and 50 healthy people. The KOS-B Questionnaire, the IVE Questionnaire, the SES Scale, the SPP-25 Scale, the Delta Questionnaire and the APSZ questionnaire were used in the research. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. In the group of patients with osteoarthritis, the leading correlates of indebtedness are: assessment of the stress situation related to the current economic situation seen as a threat, and perceiving it as harm or loss. In the healthy group, the leading correlates of incurring financial liabilities are impulsiveness, self-esteem, assessment of the stress situation related to the current economic situation seen as a threat, openness to new experiences and sense of humor, empathy, and the need for social approval. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. In the group of patients with osteoarthritis, the factor conducive to incurring financial liabilities is the assessment of the stressful situation related to the current economic situation seen as a threat, while perceiving it as harm or loss leads to abandoning reliance on credit. In the healthy group, the factors that favor this type of activity are impulsiveness, self-esteem, the assessment of the stress situation related to the current economic situation seen as a threat and the need for social approval; the factors protecting against indebtedness in healthy persons are openness to new experiences and sense of humor as well as empathy.